α-Pyrrolidinohexanophenone (α-PHP) and α-Pyrrolidinoisohexanophenone (α-PiHP): A Review - Pedro Dinis; João Franco; Cláudia Margalho (Life, 2024)
New Psychoactive Substances are currently a serious and growing problem affecting public health worldwide. By 2022, 1184 of these substances had been identified over a period of 16 years. Within these, α-pyrrolidinohexanophenone (α-PHP) and α-pyrrolidinoisohexanophenone (α-PiHP) have emerged, two synthetic cathinones from the pyrovalerone derivates subgroup that are positional isomers of each other. Alpha-PHP appeared on the Japanese illicit drug market in 2014 and, two years later, α-PiHP was identified for the first time in China. They were placed in schedule II on the list of Psychotropic Substances under International Control in 2020 and in March 2023, respectively. Both cathinones have no therapeutic potential for medical use and therefore are abused for recreational habits, which can lead to fatalities. The most frequent adverse effects reported are cardiac, psychiatric, and neurologic, and fatal intoxications have already been described. In Portugal, their consumption and consequent seizures are more prevalent on the archipelagos, which has been aggravating the health situation. In conclusion, these types of substances are a challenge for forensic toxicology since they are easily synthesized, modified, and placed on the market. Therefore, more studies to develop analytical methods to detect them and more comprehensive legislation should be applied. Thus, this review aimed to address the legislative, physicochemical, toxicological, and analytical aspects of both substances.